A Comparative Study of Dark Matter in the MSSM and Its Singlet Extensions: A Mini Review. (24th October 2012) - Wang, Wenyu
Abstract : In this note we briefly review the recent studies of dark matter in the MSSM and its singlet extensions: the NMSSM, the nMSSM, and the general singlet extension. Under the new detection results of CDMS II, XENON, CoGeNT, and PAMELA, we find that (i) the latest detection results can exclude a large part of the parameter space which is allowed by current collider constraints in these models. The future SuperCDMS and XENON can cover most of the allowed parameter space; (ii) the singlet sector will decouple from the MSSM-like sector in the NMSSM; however, singlet sector makes the nMSSM quite different from the MSSM; (iii) the NMSSM can allow light dark matter at several GeV to exist. Light CP-even or CP-odd Higgs boson must be present so as to satisfy the measured dark matter relic density. In case of the presence of a light CP-even Higgs boson, the light neutralino dark matter can explain the CoGeNT and DAMA/LIBRA results; (iv) the general singlet extension of the MSSM gives a perfect explanation for both the relic density and the PAMELA result through the Sommerfeld-enhanced annihilation. Higgs decays in different scenario are also studied.